INTERNET ELECTROCARDIOGRAPHY IN PEDIATRICS - E. V. Timofeev (Juvenis Scientia, 2021)
Introduction. Internet electrocardiography (internet-ECG) is becoming one of the most demanded areas of telemedicine; it becomes especially important in conditions of remoteness from medical and diagnostic institutions and impossibility of real consulting assistance of specialists. The general principle of operation of the internet-ECG devices is transferring the record to a server with subsequent processing and obtaining an automatic conclusion on the rhythm and morphology of the atrial-ventricular complex. At present, internet-ECG is widely used in adult network, while its possibilities in pediatrics are poorly covered. Materials and methods. The archive of children's ECGs recorded using the Cardiometer-MT system in the period from 2013 to 2021 has been analyzed. 3 groups of children were identified. 1st — screening of practically healthy children of primary school age (2153 children), 2nd group — school-age children examined in children's city polyclinics, who underwent stress and vegetative tests (2500 children), 3rd group — 200 healthy full-term newborn children who had a standard resting ECG on 1-2 days of life. Results. The advantages of using such systems in the mass examination of children of various ages in the framework of screening programs are shown. The results of an ECG examination of 2153 healthy children of primary school age are presented. The results of the automatic and medical conclusion are compared, sensitivity and specificity in the detection of cardiac arrhythmias and conduction are determined. The advantages of internet-ECG in carrying out vegetative and stress tests in the examination of adolescent children are substantiated. Performance of functional (including vegetative) and stress tests using internet-ECG systems allows to estimate reliably the functional state of the cardiovascular system, to determine adaptive capabilities of the vegetative nervous system, to reveal hypertension at early stages. Conclusion. The internet-ECG makes it possible to significantly simplify and streamline the ECG examination of children, forming an electronic archive of records, which is relevant for field examinations in children's groups and in conditions of a shortage of qualified specialists in functional diagnostics.